Natural Products To Combat Autoimmune Disorders (Journal of Pharmaceutical Negative Results, 2022)
Autoimmune disorders represent a complex and often challenging group of diseases in which the immune system mistakenly targets the body's own cells and tissues. While conventional medical treatments are crucial in managing these conditions, there is growing interest in complementary and natural approaches to alleviate symptoms and improve overall well-being. This article provides an overview of various natural products, such as turmeric, ginger, omega-3 fatty acids, probiotics, and others, that have shown promise in supporting individuals with autoimmune disorders. We explore their potential benefits, the limitations of natural remedies, and the importance of consulting healthcare professionals to create a holistic and personalized treatment plan. While natural products can play a role in combatting autoimmune disorders, they should always complement, not replace, established medical therapies, with a focus on improving the quality of life for those affected by these complex conditions.